PERCEPÇÃO SÓCIOAMBIENTAL DO CULTIVO DE PINHÃO MANSO PARA PRODUÇÃO DE BIODIESEL NO MÉDIO VALE DO RIO PARAÍBA DO SUL, RJ. - Pinto, Cláudio Luis Souza (2010)
This paper aims to contribute to environmental sustainability regarding new alternative energies. In the current context Agroenergy reaches a new importance in world politics with the use of renewable biomass for biofuel production by replacing the original fossils, for example, the Oil. It is intended by reviewing the literature, identifying actions that seek to minimize environmental impacts and proposals for sustainability in the use of clean or renewable energy. Also, the objective is to use a reviewed literature to identify initiatives, research new technologies, programs to encourage the production of biodiesel permeating the reduction of environmental impacts without curb global development. Two studies on the cultivation of Jatropha for biodiesel production in the middle Paraíba do Sul valley are presented.